Optimization of Cinnamaldehyde Production from Cinnamon Leaf (Cinamomum burmanii Nees ex BI - Yustina Wuri Wulandari; Purnama Darmadji; Budi Rahardjo (Indonesian Association of Food Technologists, 2003)
Cinnamaldehyde was the major constituent of the hark and leaf oil of Cinnamomum burmannii Blume. The first production of C. hurmannii is the hark powder for flavoring industry and the second product is essential oil. The essential oils as well as cinnamon flavor is a potent antimicrobial and antifugal activities, ayuverdic medicine and the antipyretic. The production and functional properties of essential oil from bark or leaf of C. hurmannii depend on cinnamaldehyde content. The objective of this experiment was to establish optimum processing condition of cinnamaldehyde production from cinnamon leaf. The essential oil ofcinnamon leaf was produced by water and steam distillation method with three factor experiments: bulk density, power distillation and distillation time. The Optimal gf. three factor process were evaluated using Response Surface Methodology with mathematic, statistic and matlab programs. The result showed that the optimal production of cinamaldehyde compound from the leaf oft:. burmannii were producing at hulk density 16.769 kg./m3. power to produce of steam 1252 watt, and distillation time 3,027 hour.